Improving Continuous Assessment Practice in Nigerian Schools - Bandele, S. O.; Ayodele, C. S. (Advances in Social Sciences Research Journal, 2015)
The paper examined the improvement of continuous assessment (CA) practice in Nigerian Schools to enhance teaching and learning. CA is a holistic approach that systematically obtains information about the knowledge, interest, attitude, behavior, skills and potentials of learners. This is done at predetermined intervals to reap the benefits of CA. Teachers, parents, principals’ and Ministry of education officials commitments to its use should be revived. The practice of CA should be monitored and should provide opportunity for feedback to students, parents and stakeholders.